2018
DOI: 10.2502/janip.68.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre- and post-reinforcer delays on choice in pigeons

Abstract: The present study examined effects of pre-and post-reinforcer delays on pigeons' choice using concurrent-chains schedules. Subjects were exposed to concurrent-chains schedules in which a single variable-interval 30-s schedule was arranged for the initial link, followed by different fixed-time schedules for pre-and post-reinforcer delays as the terminal links. The pre-and post-reinforcer delays were fixed at 2 s for one alternative and they were manipulated across conditions (2 s, 8 s, 20 s, or 40 s) for the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This is in line with observations that several animal species exhibit a level of self-control that is best explained by maximization of the short-term reward rate, which is insensitive to PRD and ITI (i.e., reward amount divided by reward delay; starlings [ Sturnus vulgaris ]: Bateson & Kacelnik, 1996; blue jays [ Cyanocitta cristata ]: Stephens & Anderson, 2001; tamarins [ Saguinus oedipus ]: Stevens et al, 2005). Indeed, some studies have shown that animals are sensitive to PRD to some extent, but the sensitivity to PRD is much smaller than the sensitivity to the reward amount and delay (e.g., pigeons [ Columba livia ]: Hata & Saeki, 2018; Logue et al, 1985; rats [ Rattus norvegicus ]: Yamaguchi et al, 2015). If the difference in PRD between two options is ignored, the long-term reward rate obtained by choosing either option would be misestimated, which may be consistent with the hyperbolically discounted value derived from ITC behavior in many species (Hwang et al, 2009; Kirby & Maraković, 1995; Mazur & Biondi, 2009).…”
mentioning
confidence: 99%
“…This is in line with observations that several animal species exhibit a level of self-control that is best explained by maximization of the short-term reward rate, which is insensitive to PRD and ITI (i.e., reward amount divided by reward delay; starlings [ Sturnus vulgaris ]: Bateson & Kacelnik, 1996; blue jays [ Cyanocitta cristata ]: Stephens & Anderson, 2001; tamarins [ Saguinus oedipus ]: Stevens et al, 2005). Indeed, some studies have shown that animals are sensitive to PRD to some extent, but the sensitivity to PRD is much smaller than the sensitivity to the reward amount and delay (e.g., pigeons [ Columba livia ]: Hata & Saeki, 2018; Logue et al, 1985; rats [ Rattus norvegicus ]: Yamaguchi et al, 2015). If the difference in PRD between two options is ignored, the long-term reward rate obtained by choosing either option would be misestimated, which may be consistent with the hyperbolically discounted value derived from ITC behavior in many species (Hwang et al, 2009; Kirby & Maraković, 1995; Mazur & Biondi, 2009).…”
mentioning
confidence: 99%